To the Right Honourable John Lord Sommers Baron of Evesham in ye county of Worcester President of Her Majesty's most Honourable Privy Council etc. This Map of North America According to ye Newest and most Exact Observations is most Humbly Dedicated by your Lordship's most Humble Servant Herman Moll Geographer - Moll, Herman d. 1732 (Bowles, John 1701-1779 Bowles, Thomas d. 1767 Overton, Philip d. 1751 King, John [mapseller], 1719)
18th century Copper engraving handcolored with watercolor. Outline color. Mounted on linen. Relief shown pictorially. Printed in cartouche in upper left corner: "To the Right Honourable John Lord Sommers Baron of Evesham in ye county of Worcester President of Her Majesty's most Honourable Privy Council etc. This Map of North America According to ye Newest and most Exact Observations is most Humbly Dedicated by your Lordship's most Humble Servant Herman Moll Geographer." Printed along top border: "Sold by H. Moll over against Devereux Court in ye Strand. Printed for I. Bowels Print & Mapseller at the Black Horse in Cornhill and T. Bowles Print and Mapseller next to the chapter house in St. Pauls Churchyard, and over against Devereux Court, without Temple Bar. And by P. Overton Map and Printseller near St. Dunstans Church Fleetstreet. And by John King at the Globe in the Poultry." Printed within banner family coat of arms atop the title cartouche: "Prodesse Quam Conspici." Printed along bottom of title cartouche beneath illustration of plants and rice: "B. Lens delin. G. Vertue Sculp." Beneath title cartouche is an illustration depicting the cod fishing industry with the following printed key describing each step of the industry: "A view of a Stage 7 also of ye manner of Fishing for Curing & Drying Cod at New Found Land." "A. The Habit of ye Fishermen. B. The Line. C. The Line. D. The Dressers of ye Fish. E. The Trough into which they throw ye Cod when Dressed. F. Salt Boxes. G. The manner of Carrying ye Cod. H. The Cleansing ye Cod. I. A Press to extract ye oyl from ye Cods Livers. K. Casks to receive ye water & Blood that comes from ye Livers. L. Another Cask to receive the Oyl. M. The Manner of Drying of Cod." Printed in the lower left corner of the map are 10 inset maps of various ports and bays including St. John's Harbor, "Boston Harbor, New York City harbor, Charlestown, Port Royal Harbor, Havana, Porto Bella bay, Vera Cruz, Cartagena harbor, and the port of Acapulco. Printed in the northwest part of modern-day United States above Great Salt Lake in "Mozeemleck Country": "The Baron Lahontan in his first Book Pag: 125 says that some of the Mozeemleck nation told him that at the distance of 150 Leagues, their principal River empties it self into a Salt Lake 300 Leagues in circumference, the mouth of wich is about two Leagues broad. That ye lower part of that River is adorn'd with six noble Cities besides a hundred Towns, great an small, round that sort of Sea, and that ye People call themselves Tahuglank etc." Printed above the Tropic of Cancer next to the right edge: "NB. You will find Florida in this Map called Louisiana: The R. Misisipi, R. St. Louis; Massacre Port & Haven of ye Isl. Dauphine; le Missiours R., R. St. Philip; Ouabach R., R. St. Jerom; For thus ye French have altered ye Names in ye Kings Grant of those Countries to Mons. Crozat, date Sept. 14, 1712." Printed in lower right corner is a key explaining points of the trade routes of Spanish Galleons: "Explanation. A. Here one of the Flota drops Anchor to give notice to R. de la hacha, that the Galeons are come, and immediately Expresses are sent over Land to Cartagena, Lima, Panama etc to hasten the Kings Treasure. B. At Cartagena ye Galeons usually stay 60 days, and thence go to Portobel where they lye 30 days, and then return again to Cartagena; from whence after som stay, they sail for ye Havana, to meet there ye Flota, which is a small number of Ships, that go to la Vera Cruz to take in ye Effects of that Country." Written in pencil in lower left corner: "1709-1720." Written in pencil in upper right corner: "1715." The North Atlantic Ocean is called the "Western Ocean" and the Pacific Ocean is labeled as the "South Sea." The Caribbean Sea is called the "North Sea." Depicts California as an island with the sea between California and the west coast of North America labeled as, "Gulf of California or Red Sea." The "Mozeemleck Country" is shown in the northwest of modern-day United States as is Great Salt Lake. The "Straits of Annian" are shown along the coast of Mozeemleck Country. A river connects Great Salt Lake to the Mississippi River. The French claim of Louisiana has been reduced on this English map to south of the Ohio River though it still stretches as far east as the Appalachian Mountains. The Great Lakes, Hudson's Bay and Baffin's Bay are all depicted. However, Baffin's Bay appears far narrower than it actually is and a note on the map shows another border of Baffin's Bay stating, "Some will have Baffins Bay to run West as far as this feint Shaddow." Labrador is named "New Britain" and the Eskimo or "Eskimaux" are shown to reside there. New York is shown as north and west of Button's Bay. Northern California is depicted as "New Albion" with the following legend: "New Albion is laid down Acording to the Observations maed by Sr. Francis Drake A.D. 1578." The far northwest region and north of North America as well as the northwest of modern-day United States is labeled as "Parts Unknown." Just south of this region is "Quivira." Some of the British colonies are labeled including Virginia, Maryland, New Jersey, Pennsylvania, New York and New England as well as modern-day Maine or "New Scotland." The ocean along the northeast coast of modern-day United States is labeled as the "Sea of the British Empire." Just west of Hudson's Bay is an area called "The Bogs Morasses & Lakes of the Assinipovals." The Azores are shown in the Atlantic Ocean and Ireland and Iceland are visible. Areas where Native American tribes live are labeled including the Sioux, the Natchez, and the Eskimo. The routes of Captain Thomas James (1593?-1635?) in 1631 and Captain Henry Hudson (1565-1611) are shown in the north Atlantic Ocean and around Hudson's Bay. The routes of Spanish Galleons are shown through the Gulf of Mexico, stopping at Cartagena and Havana. A compass rose appears in the north Atlantic Ocean. The title cartouche depicts Eskimo on the right and natives from a tropical region on the left. Birds are depicted on either side of the cartouche and a native is shown reclining in front of the cartouche with a bow, a bowl of grain, plants, and a small pot of gold. Of note, the coloring of the borders along the northwest coast seems to depict an alternate mapping of the northwest coast than that provided by the engraving. Scale: c.a. 1:12,000,000. Herman Moll (?-1732) was a Dutch cartographer, engraver and bookseller. Moll first came to England in 1678. He worked as an engraver for Moses Pitt, Greenville Collins, John Adair, and Seller and Price. Some of his work includes "America and Europe" for Moore's "Geography" (1681), six charts for Collins in 1689, "A System of Geography" (1701), "Globe" (1703), "Atlas Minor" (1727, 1729), and "World Described" (1727) (Tooley, 444). He was a major proponent of the concept that California was an island even after exploration information from Jesuit Father Kino revealed that California was a peninsula in 1705. Many of Moll's maps were used by the British to contest France's claims on certain land borders following the War of Spanish Succession (1702-1713) (Portinaro and Knirsch, 317). This particular map shows a number of geographical errors and misconceptions regarding North America. Moreover, it exemplifies the tension between the British and the French over their claims on territory. Wheat is particularly critical of this map, noting that it shows terrible "pitfalls." First, it shows California as an island, following Sanson's map of 1656 (Wheat, 69; Goss, 118). Second Moll depicts New Mexico "crowded over toward the Gulf of California" (Wheat, 69). Third, the map paints the "Mozeemleck Country" as far out to the west, almost by the Strait of Annian (69). Ermen notes another critique of this map in the depiction of Great Salt Lake as flowing into the Mississippi River (39). Yet, the map also offers some unique perspectives in the form of its many inset maps of Boston, New York City, Charlestown, Port Royal, St. John's , Havana, Portobello, Vera Cruz, Cartagena and Acapulco (Goss, 118; Schwartz and Ehrenberg, 140). Tooley notes that the map is similar to Sanson's work but has extra additions such as "Mounts Nevada and St. Martin, P. de Sardines, and towns in the south, La Conception, St. Nicholas, St. Isidore and Gigante" (Tooley, "California…", 130). Politically speaking, the map is key in its depiction of British claims. Goss writes that this map responds to Guillaume de l'Isle's map of 1718, "Carte de la Louisiane" which shows Louisiana stretching across to the Appalachians. In this map, Moll cuts the French territory to "south of Ohio river" and enforces English claims on Labrador and the area surrounding Hudson's Bay in accordance with the Treaty of Utrecht (1713). The map also offers an unusual depiction of the codfishing industry in Newfoundland (Goss, 118; Schwartz and Ehrenberg, 140). Source(s): Ermen, Eduard Van. "The United States in Old Maps and Prints. Wilmington, DE: Atomium Books, Inc., 1990. Goos, John. "The Mapping of North America: Three Centuries of Map-making 1600-1860." London: Wellfleet Press, 1990. McLaughlin, Glen and Nancy H. Mayo. "The Mapping of California as an Island: An Illustrated Checklist." Saratoga, CA: California Map Society, 1995. Portinaro, Pierluigi and Franco Knirsch. "The Cartography of North America 1500-1800." New York: Facts on File, Inc., 1987. Schwartz, Seymour I and Ralph E. Ehrenberg. "The Mapping of America." New York: H. N. Abrams, 1980. Tooley, Ronald Vere. "Chapter 3: California as an Island: A Geographic Misconception Illustrated by 100 Examples from 1625 to 1770." In "The Mapping of America." Ed. by Ronald Vere Tooley. London: Holland Press, 1985. 110-134. ---. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wagner, Henry R. "The Cartography of the Northwest Coast of America to the year 1800 Volume 2." Berkeley: University of California Press, 1937. Wheat, Carl I. "Mapping the Transmississippi West." Volume 1. San Francisco: Institute of Historical Cartography, 1957.